(3jGbhJI GdfSH GdhgGLIs - (3GdYQHqj Hf YHO GdbGOQ Hf Ydj GdMSfj GdGOjSj, CHh MGeO GdeTQaj,J (B1313 (3g` s
(3ChdgG (B:s
(3hHYO , deG QCjJ MH Bd GdfHi ef CYXe GdhSGFd YfO Gddg MQcfi HGYK GdMH Cf CLeY JCdjakG jSege HGdJYQja s
(3BNQgG (B:s
(3efi GdSdGoe Ydjce eGQfMJ QjM GdUHG ZUfG hgnH TeGod s
(3heLGLI gPG cGf QkL UGdMkG HGdbUQ GdLRGFQj aj ChGSW GdbQf GdMGOj YTQs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B224s
(3Odjd eDQN GdeZQH (B- (3U (B146 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B477 s
Keywords: (3GdJGQjNs